The German Margarete defensive line from World War II in southwestern Slovakia. Archaeological evidence and historical facts - Pavol Šteiner; Jozef Kónya (Archeologia Polski)
Research on field fortifications from World War II in Slovakia has led to the identification of the Margareten-Stellung, a German defensive line, a part of which has now been located east of the town of Šahy where the Soviets engaged the retreating Germans in mid-December 1944. The identification was based on references from written sources and LIDAR images of the woodlands near the town. A survey of this system has contributed insights into its technical design, tactical significance and the role it played in the battle of Šahy. Research on features of this kind brings them into the public eye, allowing them to be registered as archaeological sites and developed as historical heritage sites.